Characteristics of Imperial College London's COVID‐19 research outputs. Issue 3 (12th January 2021) - Price, Robyn; Ozkan, Yusuf
Abstract: We identified 651 research outputs on the topic of COVID‐19 in the form of preprint, report, journal article, dataset, and software/code published by Imperial College London authors between January to September 2020. We sought to understand the distribution of outputs over time by output type, peer review status, publisher, and open access status. Search of Scopus, the institutional repositories, Github, and other databases identified relevant research outputs, which were then combined with Unpaywall open access data and manually‐verified associations between preprints and journal articles. Reports were the earliest output to emerge [median: 103 days, interquartile range (IQR): 57.5–129], but journal articles were the most commonly occurring output type over the entire period (60.8%, 396/651). Thirty preprints were identified as connected to a journal article within the set (15.8%, 30/189). A total of 52 publishers were identified, of which 4 publishers account for 59.6% of outputs (388/651). The majority of outputs were available open access through gold, hybrid, or green route (66.1%, 430/651). The presence of exclusively non‐peer reviewed material from January to March suggests that demand could not be met by journals in this period, and the sector supported this with enhanced preprint services for authors. Connections between preprints and published articles suggests that some authors chose to use both dissemination methods and that, as some publishers also serve across both models, traditional distinctions of output types might be changing. The bronze open access cohort brings widespread 'free' access but does not ensure true open access.